Influence of Awareness, Penalties, Socialization, and Authority on Vehicle Tax Compliance in Situbondo - Qomari, Muhammad Abdullah; Laksmi, Ayu Chairina (E-Jurnal Akuntansi; Vol 35 No 2 (2025), 2024)
This study aims to analyze the influence of tax awareness, tax sanctions, tax socialization, and the authority's power on the compliance of motor vehicle taxpayers in Situbondo Regency, East Java. Using the Theory of Planned Behavior (TPB) as a theoretical framework, this research investigates how these factors contribute to taxpayers' compliance behaviors. Data were collected from 100 respondents through surveys and analyzed using multiple linear regression. The results indicate that tax awareness, tax sanctions, tax socialization, and the authority's power significantly affect taxpayer compliance. These findings suggest that improving these factors can enhance tax compliance among motor vehicle owners in Situbondo Regency. Keywords: Tax Awareness;Tax Sanctions; Tax Socialization; Authority's Power; Tax Compliance.